Physical activity is associated with functional capacity of older women with osteosarcopenic obesity: 24-month prospective study - dos Santos, Vanessa Ribeiro [UNESP]; Gobbo, Luís Alberto [UNESP] (Springer Nature, 2020)
Background/Objectives: Physical activity (PA) could be effective in the prevention of functional disability in older women, especially for those with body composition abnormalities. The aim this study was to analyze the association of total PA and in different domains with physical function and functional capacity in older women with or without osteosarcopenic obesity (OSO), as well as to assess the risk of functional disability in osteosarcopenic obesity older women insufficiently active. Subjects/Methods: The study included 152 Brazilian older women, aged 60 years and older. Body composition was measured by dual energy X-ray absorptiometry (DXA) and physical function by physical tests. Functional capacity and PA were self-reported. Results: In older women without OSO, the practice of leisure-time exercise (β:−0.23; 95%CI −0.40 to −0.06) and total PA (β:−0.40; 95%CI −0.57 to −0.23) is inversely associated with dependence in ADL. In older women with OSO, the practice of leisure-time exercise was inversely associated with physical function (β:0.88; 95%CI 0.31–1.46) and functional capacity (β:−1.05; 95%CI 1.64 to −0.45), while total PA (β:−1.03; 95%CI −1.93 to −0.13) was inversely associated with functional capacity, independent of control variables. In addition, older women with OSO who remained insufficiently active in leisure-time exercise (HR:2.28; 95%CI 1.04–4.99) and locomotion (HR:2.62; 95%CI 1.28–5.36) domains presented risk for functional disability. Conclusions: PA is inversely associated with physical function and functional capacity in older women with or without OSO, and older women with OSO who are insufficiently active in leisure-time exercise and locomotion domains presented a higher risk for functional disability.